Muscle fascicle behavior during eccentric cycling and its relation to muscle soreness - Penailillo, L.; Blazevich, A.; Nosaka, K. (Medicine & Science in Sports & Exercise, 2015)
A single bout of eccentric exercise confers a protective effect against muscle damage and soreness in subsequent eccentric exercise bouts, but the mechanisms underpinning this effect are unclear.